Underuse and Overuse of Osteoporosis Screening in a Regional Health System: a Retrospective Cohort Study - Amarnath, Anna Lee D. (J Gen Intern Med, 2015)
BACKGROUND: The United States Preventive Services Task Force (USPSTF) recommends screening for osteoporosis with dual-energy x-ray absorptiometry (DXA) for women aged ≥ 65 years and younger women with increased risk. “Choosing Wisely” initiatives advise avoiding DXA screening in women younger than 65 years without osteoporosis risk factors. OBJECTIVE: We aimed to determine the extent to which DXA screening is used in accordance with USPSTF recommendations within a regional health system. DESIGN: This was a retrospective longitudinal cohort study within 13 primary care clinics in the Sacramento, CA region. PATIENTS: The study included 50,995 women aged 40–85 years without prior osteoporosis screening, diagnosis, or treatment attending primary care visits from 2006 to 2012, observed for a mean of 4.4 years. MAIN MEASURES: We examined incidence of DXA screening. Covariates included age, race/ethnicity, and osteoporosis risk factors (body mass index < 20, glucocorticoid use, secondary osteoporosis, prior high-risk facture, rheumatoid arthritis, alcohol abuse, and current smoking). KEY RESULTS: Among previously unscreened women for whom the USPSTF recommends screening, 7-year cumulative incidence of DXA screening was 58.8 % among women aged 60–64 years with ≥ 1 risk factor (95 % CI: 51.9–65.8 %), 57.8 % for women aged 65–74 years (95 % CI: 55.6–60.0 %), and 42.7 % for women aged ≥ 75 years (95 % CI: 38.7–46.7 %). Among women for whom the USPSTF does not recommend screening, 7-year cumulative incidence was 45.5 % among women aged 50–59 years (95 % CI 44.1–46.9 %) and 58.6 % among women aged 60–64 years without risk factors (95 % CI 55.9–61.4 %). CONCLUSIONS: DXA screening was underused in women at increased fracture risk, including women aged ≥ 65 years. Meanwhile, DXA screening was common among women at low fracture risk, such as younger women without osteoporosis risk factors. Interventions may be needed to augment the value of population screening for osteoporosis.